(2;-2)
Пошаговое объяснение:
х²+4у+4=0,
у²-4х+4=0;
:х²+4у+4=0,
-
у²-4х+4=0;
х²+4у+4-(у²-4х+4)=0
х²+4у+4-у²+4х-4=0
х²+4у-у²+4х=0
(х²-у²)+(4у+4х)=0
(х-у)(х+у)+4(у+х)=0
(х-у+4)(х+у)=0
х-у+4=0 или х+у=0
1) х-у+4=0у = х+4
х²+4у+4=0 →
х²+4(х+4)+4=0
х²+4х+16+4=0
х²+4х+20=0
Д=4²-4*1*20=16-80=-64<0 → нет решений
2) х+у=0х=-у
х²+4у+4=0
(-у)²+4у+4=0
у²+4у+4=0
Д=4²-4*1*4=16-16=0
у=-4/(2*1)=-4/2=-2
х=-у=-(-2)=2 → ответ: (2; -2)
:х²+4у+4=0,
+
у²-4х+4=0;
х²+4у+4+(у²-4х+4)=0
х²+4у+4+у²-4х+4=0
(х²-4х+4)+(у²+4у+4)=0
(х²-2*х*2+2²)+(у²+2*у*2+2²)=0
(х-2)²+(у+2)²=0
так как а²≥0 при любом а, то (х-2)²≥0, (у+2)²≥0 →
(х-2)²+(у+2)²=0 при (х-2)²=0 и (у+2)²=0 или
х-2=0 и у+2=0, то есть х=2, у=-2 → ответ:(2;-2)